Investigation of Factors Influencing Rise in Needle Temperature to Enhance the Production and Seam Performance –part I - Shradhanjali Mohapatra; Priyalatha S; Indu G K; Benitta Christy P; Paranthaman R; Saravanan K; Kubera Sampath Kumar S; Prakash C (Journal of Natural Fibers, 2022)
The most recent industrial sewing machines are designed and developed to give high production and quality. These machines are capable to operate at very high speed. On the other hand, the sewing machines operated at high speed are facing the challenge of very high needle temperature generation which leads to seam damages like burnt holes, stiff seam, molten seam etc. Such seam damages are serious issue and affects the performance of the garment produced. An attempt was taken to analyze the factors influencing the rise in needle temperature change during sewing to derive exact solution to the problem. Thermal camera was set up in the sewing machine and change in needle temperature under varying influencing parameter was recorded and taken for analysis. From this study, it is found that twill fabric and interlock fabric with superimposed seam of four layers and high needle tension produced higher needle temperature. The other factors such as sewing thread, stitch density, needle size etc falls in next level of contribution.